A low-cost contact system to assess load displacement velocity in a resistance training machine - Busca, B.; Font, A. (Journal of Sports Science & Medicine, 2011)
This study sought to determine the validity of a new system for assessing the displacement and average velocity within machine-based resistance training exercise using the Chronojump System. The new design is based on a contact bar and a simple, low-cost mechanism that detects the conductivity of electrical potentials with a precision chronograph. This system allows coaches to assess velocity to control the strength training process. A validation study was performed by assessing the concentric phase parameters of a leg press exercise. Output time data from the Chronojump System in combination with the pre-established range of movement was compared with data from a position sensor connected to a Biopac System. A subset of 87 actions from 11 professional tennis players was recorded and, using the two methods, average velocity and displacement variables in the same action were compared. A t-test for dependent samples and a correlation analysis were undertaken. The r value derived from the correlation between the Biopac System and the contact Chronojump System was >0.94 for all measures of displacement and velocity on all loads (p < 0.01). The Effect Size (ES) was 0.18 in displacement and 0.14 in velocity and ranged from 0.09 to 0.31 and from 0.07 to 0.34, respectively. The magnitude of the difference between the two methods in all parameters and the correlation values provided certain evidence of validity of the Chronojump System to assess the average displacement velocity of loads in a resistance training machine.